Understanding ecosystems - Berube, Ryck.; Nolan, Mary Lee.; Nolan, Sydney; oare, Thomas F. (Thomas Fulton), 1936-; Russell, George H.; Educational Video Network, Inc. (Huntsville, Tex. : Distributed by Educational Video Network, 1994)
Ecosystems can range in size from tidal pools to the entire planet. Understanding the boundaries of various collections of organisms is the first step toward maintaining the balance to preserve them.
Videography, Sydney & Mary Lee Nolan; editor, Ryck Berube; narrator, Thomas F. Soare; executive producer, George H. Russell.
Keywords: Biotic communities; Ecology -- Videocassettes; Science films